Application of smart technologies in organic farming: recent advances and future directions - Pakeerathan, K. (University of Jaffna, 2025)
Smart farming is the use of information technology and sensors to collect and analyze data about crops, soil and weather conditions to make informed decisions about crop management, such as when to irrigate, apply fertilizer or control pests and diseases. The application of SMART technologies in organic farming is a relatively new field, but there have been some recent advances that have the potential to improve the sustainability and efficiency of organic production. The future of SMART technologies in organic farming is promising. As these technologies continue to develop, they will provide organic farmers with new tools to improve their yields, reduce their environmental impact, and make their operations more sustainable. This chapter reports current developments and applications of SMART technologies such as sensor technology, biotechnology, nanotechnology and information communication technology, etc., in organic agriculture and blooming technologies for scientists and students who are working in the field to use this chapter as reference material.
Keywords: Nano-biotechnology; Organic farming; Plant protection; Sensors; SMART technologies